Gestational trophoblastic neoplasia (invasive mole) following incomplete abortion- a rare case presenting with uterine perforation with gross hemoperitoneum: A case report - Neupane, G; Acharya, S (Journal of Chitwan Medical College, 2017)
Invasive mole is gestational trophoblastic neoplasia, characterized by aggressive invasion of the wall of the uterus by the trophoblastic cells. Here, we report a rare case of 17 years primigravida who presented with per vaginal bleeding and uterine perforation with gross hemoperitoneum about 1 month of manual vacuum aspiration of incomplete abortion. Resuscitation followed by emergency laparotomy with subsequent repair of uterine perforation was done. The patient received a total of 5 cycles of single agent chemotherapy (Methotrexate with leukovorin rescue). The beta hCG level became normal after 3 cycles of chemotherapy and further 2 cycles chemotherapy was administered. She was followed up for another 1 year in which her beta hCG levels were within normal limits.